Análisis comunicacional de los contenidos del noticiario de radio Ovación 105.5 fm, y su impacto social en la ciudadanía del cantón Machala, año 2014. - Arias Vivanco, Germán Anival (2015)
This paper entitled COMMUNICATIONAL ANALYSIS OF THE CONTENTS OF THE NEWS RADIO 105.5 FM OVATION, AND SOCIAL IMPACT ON CITIZENSHIP OF CANTON MACHALA, 2014, is aimed at investigating the operational performance of Ovation Radio 105.5 FM, treatment news content and social contribution that gives the machaleña citizenship.